Student Financial Management Behavior: Factors Potential - Santus, Antonius; Erawati, Teguh (Yayasan Riset dan Pengembangan Intelektual, 2024)
Financial behavior is an individual's ability to manage (planning, budgeting, checking, managing, controlling, disbursing, and storing) daily finances is one of the most talked about. This research focuses on